Design principles for density functionals using a linear expansion - Ayoub Aouina; Matteo Gatti; Lucia Reining (npj Computational Materials)
Abstract Density Functional Theory is one of the most widely used theoretical approaches for the calculation of properties of materials, but the systematic development of new functionals with controllable accuracy is an ongoing challenge. We propose to use perturbation theory around the homogeneous electron gas in a way that is optimized using physical insight, and to combine it with the recently developed connector approach in order to satisfy an exact limit. In this way, we develop an explicit non-local density functional for the Kohn-Sham exchange correlation potential. First results for the self-consistently calculated charge density and potential for three prototype materials demonstrate which accuracy can be reached for the charge density, confirm the systematicity of the approach, and suggest directions for further improvement.